ANALISIS STRATEGI PEMASARAN WISATA SEJARAH (Rumah Bung Karno dan Rumah Fatmawati) DI KOTA BENGKULU - Afriani, Sulisti; Susanti, Neri (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2017)
Sulisti Afriani dan Sulisti Afriani: The purpose of this study was to determine the SWOT analysis is applied to the marketing strategy in the House and the House Fatmawati Soekarno Bengkulu. Data collection methods used were a questionnaire method to distribute a list of questions to respondents. The analytical method used is the SWOT analysis to determine the internal factors (strengths and weaknesses) and external factors (opportunities and threats), which will then be incorporated into the SWOT matrix.The results of this study showed that factor analysis in the table